PENGARUH DISIPLIN KERJA, TURNOVER KARYAWAN, DAN KERJA LEMBUR TERHADAP PRODUKTIVITAS KERJA PADA PT LB TECHNOLOGIES BATAM - Harefa, Asria; Heryenzus, Heryenzus (SCIENTIA JOURNAL, 2019)
Human resources is the most important asset in a company or organization that affects the efficiency and effectiveness of the company, so the company is expected to manage MSDM as possible so as not to happen low productivity in a company. This research was conducted at PT LB Technologies Batam which is located in Komp Sarana Unggulan Block B No.8 Jl. Engku putri Batam Center. The purpose of this study is to determine the effect of work discipline, employee turnover and overtime work on the productivity of PT LB Technologies Batam. The population in this study as many as 140 people, in determining the sample using Slovin formula so that the sample obtained 104 people. The data were collected by distributing questionnaires using a 5-point Likert scale to measure 20 indicators consisting of 20 statements. The data analysis technique used is multiple linear regression analysis using SPSS 20 application. The result of analysis from this research indicates that work discipline has positive and significant effect to work productivity, employee turnover have positive and significant effect to work productivity, overtime work has positive and significant effect to work productivity and work discipline, employee turnover and overtime work have a positive and significant effect on work productivity. Based on the results of this study can be concluded that the variables of work discipline, employee turnover and overtime work affect work productivity of 0.750 or 75%, while the remaining 25% influenced by other factors not included in this study.